2001
DOI: 10.1124/mol.59.4.894
|View full text |Cite
|
Sign up to set email alerts
|

Sensitized Increase of Period Gene Expression in the Mouse Caudate/Putamen Caused by Repeated Injection of Methamphetamine

Abstract: Methamphetamine (MAP) causes the sensitization phenomena not only in MAP-induced locomotor activity, dopamine release, and Fos expression, but also in MAP-induced circadian rhythm. Cocaine-induced sensitization is reportedly impaired in Drosophila melanogaster mutant for the Period (Per) gene. Thus, sensitization may be related to induction of the Per gene. A rapid induction of mPer1 and/or mPer2 in the suprachiasmatic nucleus after light exposure is believed to be necessary for light-induced behavioral phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 38 publications
(42 reference statements)
7
76
2
Order By: Relevance
“…For instance, the trace amine tyramine (TA) appears to play an integral role in the development of behavioral sensitization to cocaine [38] such that circadian gene regulation, TA biosynthesis and behavioral sensitization are tightly coupled in fruit flies [2]. Interestingly, subsequent work in mammals demonstrated the importance of circadian rhythmicity for psychostimulant sensitization [1,44] and, furthermore, identified a population of high-affinity TA receptors in the ventral tegmental area [11], a focal region of DA-rich cell bodies thought to be a primary component of reward circuitry in the mammalian brain. Although trace amines like TA have historically received less experimental attention than other monoamines, there exists a large literature documenting their relationship to disturbances in affect and cognition (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the trace amine tyramine (TA) appears to play an integral role in the development of behavioral sensitization to cocaine [38] such that circadian gene regulation, TA biosynthesis and behavioral sensitization are tightly coupled in fruit flies [2]. Interestingly, subsequent work in mammals demonstrated the importance of circadian rhythmicity for psychostimulant sensitization [1,44] and, furthermore, identified a population of high-affinity TA receptors in the ventral tegmental area [11], a focal region of DA-rich cell bodies thought to be a primary component of reward circuitry in the mammalian brain. Although trace amines like TA have historically received less experimental attention than other monoamines, there exists a large literature documenting their relationship to disturbances in affect and cognition (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…The Period (Per) encodes one of the essential elements involved in the transcription/translation-based auto-regular loop of the endogenous master clock (Reppert and Weaver, 2001). Three homologues of Drosophila Per genes were subsequently identified in mice (mPer1, mPer2, and mPer3) (Albrecht, 2002), leading to great progress in elucidation of the molecular mechanism underlying circadian rhythm in the CNS.It has been shown that repeated administration of methamphetamine caused behavioral sensitization as well as sensitized expression of mPer1 (Nikaido et al, 2001). Some studies implicate a role for Per genes in drug-induced behavioral sensitization processes.…”
mentioning
confidence: 99%
“…It has been shown that repeated administration of methamphetamine caused behavioral sensitization as well as sensitized expression of mPer1 (Nikaido et al, 2001). Some studies implicate a role for Per genes in drug-induced behavioral sensitization processes.…”
Section: Introductionmentioning
confidence: 99%
“…A single injection of MAP was shown to induce Period1 gene expression in the Piriform cortex (PC) and Caudate-Putamen (CPU) in the mouse brain, but not the SCN (Nikaido, Akiyama et al 2001). In addition, chronic MAP shifts the phase of circadian expression of Period1, Period2 and Bmal1 mRNA in CPU and Parietal cortex (PtA) and induces Clock mRNA expression in CPU of rats (Masubuchi, Honma et al 2000).…”
Section: Localization Of Mascomentioning
confidence: 99%
“…Administration of a high dose of MAP to intact C57BL/6 mice produces two it induces the expression of these genes in areas such as Caudate-Putamen (CPU) in mice (Nikaido, Akiyama et al 2001). Similarly, chronic MAP does not affect the Per1 expression profile in the SCN of rats ex vivo (Masubuchi, Honma et al 2000) or the firing activity of SCN neurons in vitro (Moriya, Fukushima et al 1996).…”
Section: (Nxcj IImentioning
confidence: 99%